Utilizing compassion and collaboration to reduce violence in healthcare settings - Beth A. Lown; Gary S. Setnik (Israel Journal of Health Policy Research, 2018)
Abstract Violence in healthcare settings is a global problem and violent acts are more likely to occur in emergency departments (EDs). Significant barriers to reporting workplace violence persist among healthcare workers. This, and lack of shared definitions and metrics, increase the difficulty of assessing its prevalence, understanding its causes, and comparing the impact of interventions to reduce its frequency. While risk factors for violence in EDs have been articulated, less is known about how the perspectives of patients and accompanying persons, and their interactions with ED staff may contribute to violence. We discuss the nature and social context of ED violence and some approaches used to address this problem in the U.S. We argue that perpetrators of violence as well as healthcare staff who experience ED violence suffer when it occurs. While securing safety is paramount, compassionate practices to address this suffering and the social context from which it emerges should be developed and provided for all involved. Collaboration among stakeholders, including patients and family members, may lead to effective approaches to address this problem.